A strong, tough and cost-effective biodegradable PBAT/lignin composite film via intrinsic multiple noncovalent interactions. Issue 8 (30th March 2023) - Xiong, Shao-Jun; Zhou, Si-Jie; Wang, Hao-Hui; Wang, Han-Min; Shen, Xiao-Jun; Yu, Shixin; Li, Hui; Zheng, Lu; Wen, Jia-Long; Yuan, Tong-Qi; Sun, Run-Cang
Abstract : Organic solvent fractionated lignin with low molecular weight, uniform structure and rich hydroxyl groups was completely miscible with PBAT to synthesise a strong, tough and cost-effective biodegradable composite film. Abstract : Blending lignin with industrial degradable polyester is a sustainable and economically competitive strategy for biodegradable plastic production, but the miscibility of the composite remains a great challenge. In this study, the screened lignin with low molecular weight, uniform structure and rich hydroxyl groups was completely miscible with poly(butylene adipate-co-terephthalate) (PBAT). The low molecular weight of ethyl acetate dissolved lignin (EL) was critical for decreasing its glass transition temperature and steric hindrance, and the abundance of functional groups offered plenty of sites for forming strong intermolecular interactions between EL and PBAT. The intermolecular hydrogen bonds and π–π interactions of EL and PBAT promoted the dissociation of the lignin complex, thereby enhancing the plasticizing effect of PBAT on lignin. The PBAT/EL composite film with 50 wt% EL loading (P/EL50 ) displayed high tensile strength (24.7 MPa) and elongation at break (494.7%), being ahead of the currently reported PBAT composite films with high lignin addition. The yield strength increased threefold due to the rigid lignin structure and the intrinsic multiple noncovalent interactions. Moreover, compared to pure PBAT films, P/EL50 films exhibited a higher sensitivity of the mechanical performance to temperature and had a 22.9% cost reduction.